Efficacy of Physiotherapy Interventions on Weaning in Mechanically Ventilated Critically Ill Patients: A Systematic Review and Meta-Analysis - Lippi, Lorenzo; de Sire, Alessandro; D’Abrosca, Francesco; Polla, Biagio; Marotta, Nicola; Castello, Luigi Mario; Ammendolia, Antonio; Molinari, Claudio; Invernizzi, Marco (Frontiers in Medicine, 2022)
Mechanical ventilation (MV) is currently considered a life-saving intervention. However, growing evidence highlighted that prolonged MV significantly affects functional outcomes and length to stay. In this scenario, rehabilitation strategies might have a role in improving MV duration but evidence about its efficacy in critical ill patients without chronic respiratory conditions are still lacking. Therefore, this systematic review of randomized controlled trials (RCTs) with meta-analysis aimed at characterizing the efficacy of a comprehensive rehabilitative intervention in critically ill patients. PubMed, Scopus, and Web of Science databases were systematically searched up to October 22, 2021 to identify RCTs assessing acute patients mechanical ventilated in ICU setting undergoing a rehabilitative intervention. The primary outcomes were MV duration, extubation, and weaning time. The secondary outcomes were weaning successful rate, respiratory function, ICU discharge rate and length to stay. Out of 2503 records, 12 studies were included in the present work. The meta-analysis performed in 6 RCTs showed a significant improvement in terms of MV duration (overall effect size: -3.23 days; 95% CI= -5.79, -0.67, p = 0.01; Z=2.47) in patients treated with a comprehensive rehabilitative intervention including early mobilization, positioning, airway clearance techniques, lung expansion and respiratory muscle training. The quality assessment underlined 9 studies (75%) of good quality and 3 studies of fair quality according to the PEDro scale. In conclusion, our results provided previously unavailable data about the role of comprehensive rehabilitation intervention in improving MV duration in critical ill patients without chronic respiratory conditions. Further studies are needed to better characterize the optimal combination of rehabilitation strategies enhancing the improvements in critical ill patients without chronic respiratory disorders.